Post-Adipose-Derived Stem Cells (ADSC) Stimulated by Collagen Type V (Col V) Mitigate the Progression of Osteoarthritic Rabbit Articular Cartilage - Brindo da Cruz, Isabele Camargo; Velosa, Ana Paula Pereira; Carrasco, Solange; dos Santos Filho, Antonio; Tomaz de Miranda, Jurandir; Pompeu, Eduardo; Fernandes, Tiago Lazzaretti; Bueno, Daniela Franco; Fanelli, Camila; Goldenstein-Schainberg, Cláudia; Fabro, Alexandre Todorovic; Fuller, Ricardo; et al. (Frontiers in Cell and Developmental Biology, 2021)
Collagen is essential for cartilage adhesion and formation. In the present study, histology, immunofluorescence, morphometry, and qRT-PCR suggested that adipose-derived stem cells (ADSCs) stimulated by type V collagen (Col V) induce a significant increase of type II collagen (Col II) in the degenerative area of surgical-induced osteoarthritic rabbit articular cartilage (OA). In vitro, the effects of Col V on the proliferation and differentiation of ADSC were investigated. The expression of the cartilage-related genes Col2a1 and Acan was significantly upregulated and Pou5fl was downregulated post-ADSC/Col V treatment. Post-ADSC/Col V treatment, in vivo analyses revealed that rabbits showed typical signs of osteoarthritic articular cartilage regeneration by hematoxylin and eosin (H&E) and Safranin O/Fast Green staining. Immunohistochemical staining demonstrated that the volume of Col II fibers and the expression of Col II protein were significantly increased, and apoptosis Fas ligand positive significantly decreased post-ADSC/Col V treatment. In conclusion, the expression of Col II was higher in rabbits with surgical-induced osteoarthritic articular cartilage; hence, ADSC/Col V may be a promising therapeutic target for OA treatment.